2007
DOI: 10.1897/06-511r.1
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition site selection: Pesticide avoidance by gray treefrogs

Abstract: Effects of glyphosate-formulated herbicides on nontarget organisms have received much recent attention. Although previous studies have explored the effects of pesticides on growth, development, and mortality of various amphibian species, no studies have tested the potential effects of herbicides on oviposition site selection by amphibians. Recent studies have found that a combination of pesticide and predatory cues lead to significantly increased mortality of tadpoles of several anuran species relative to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…Table 4. Weight of evidence summary for evaluating the interaction effects of coexposures to predator cues and pesticides on Ceriodaphnia dubia acute toxicity compared to the pesticides alone fenvalerate [10], endosulfan [24,34], atrazine [24], fenoxycarb [9], carbaryl [26], and glyphosate [37]. In the present study, a relatively new class of pesticide, a neonicotinoid (thiacloprid), was also found to have antagonistic interactions with predator cues on C. dubia survival.…”
Section: Interaction Between Predator Cues and Pesticidesmentioning
confidence: 50%
“…Table 4. Weight of evidence summary for evaluating the interaction effects of coexposures to predator cues and pesticides on Ceriodaphnia dubia acute toxicity compared to the pesticides alone fenvalerate [10], endosulfan [24,34], atrazine [24], fenoxycarb [9], carbaryl [26], and glyphosate [37]. In the present study, a relatively new class of pesticide, a neonicotinoid (thiacloprid), was also found to have antagonistic interactions with predator cues on C. dubia survival.…”
Section: Interaction Between Predator Cues and Pesticidesmentioning
confidence: 50%
“…Prolonged and shortened metamorphosis as well as reduced body indices were seen (Bridges, 2000;Howe et al, 2004;Cauble and Wagner, 2005;Williams and Semlitsch, 2010). Indirect effects of pesticide use included avoidance of contaminated breeding sites (Takahashi, 2007;Vonesh and Buck, 2007; but see . Exposure risks and adverse effects of pesticides are specific in three ways.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, two recent studies show that pesticides can alter oviposition site selection in some amphibians. Takahashi (2007) showed that gray treefrogs (Hyla chrysoscelis/ versicolor) completely avoid pools treated with the glyphosphate-formulated herbicide Roundup. Similarly, Vonesh and Buck (2007) show in a series of experiments that the insecticide Sevin and its active ingredient, carbaryl, also reduce oviposition in gray treefrogs across several spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%